The Role of Teachers in the English Language Learning Process at SMP Karya Sembawa, Kab. Banyuasin, Sumatra Selatan - Muhammad Bambang Purwanto (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this study is to know and describe the role of teachers in the learning process in Middle School Karya Sembawa of Sembawa. This research uses qualitative research methods with the process of collecting data using interviews, observation and questionnaires. The place of this research is SMP Karya Sembawa, Kab. Banyuasin. The sample of this study amounted to 36 people consisting of 30 students and 6 teachers. For sample student researcher uses random sampling technique (random). The results of this study indicate that in general teachers who teach in SMP Karya Sembawa, already carry out their duties and roles well but the obstacles that exist in Karya Junior High School od Sembawa still less support books books such as packages in the process of learning Indonesian.